Use of cannabidiol in the treatment of autism, review of the literature and future perspectives (Research, Society and Development, 2024)
Autism Spectrum Disorders (ASD) are considered a multifactorial disease, being associated with genetic and non-genetic causes with a predominance of development in early childhood and that compromises the cognitive, social and affective spheres, in addition to physical growth itself. There are no specific medications for autism and several medications are used to alleviate the symptoms associated with ASD, in addition there is much discussion about the use of cannabidiol. This work is a systematic review of the literature with the aim of understanding more about the use of cannabidiol to help treat patients with ASD. The results found demonstrate a strong relationship between TEA and the endocannabinoid system, especially in the CB1 and CB2 receptors. Most of the works show that the use of cannabidiol brought more benefits than side effects or adverse reactions, acting mainly in the improvement of the signs and symptoms of ASD. Therefore, it is concluded that it is of great importance to carry out more studies to clarify points that are still obscure in the use of cannabidiol in the treatment of ASD.